Impact of a Prototype Visualization Tool for New Information in EHR Clinical Documents - Farri, O.; Rahman, A.; Monsen, K.A.; Zhang, R.; Pakhomov, S.V.; Pieczkiewicz, D.S.; Speedie, S.M.; Melton, G.B. (Applied Clinical Informatics, 2012)
Background: EHR clinical document synthesis by clinicians may be time-consuming and error-prone due to the complex organization of narratives, excessive redundancy within documents, and, at times, inadvertent proliferation of data inconsistencies. Development of EHR systems that are easily adaptable to the user’s work processes requires research into visualization techniques that can optimize information synthesis at the point of care.Objective: To evaluate the effect of a prototype visualization tool for clinically relevant new information on clinicians’ synthesis of EHR clinical documents and to understand how the tool may support future designs of clinical document user interfaces.Methods: A mixed methods approach to analyze the impact of the visualization tool was used with a sample of eight medical interns as they synthesized EHR clinical documents to accomplish a set of four pre-formed clinical scenarios using a think-aloud protocol.Results: Differences in the missing (unretrieved) patient information (2.3±1.2 [with the visualization tool] vs. 6.8±1.2 [without the visualization tool], p = 0.08) and accurate inferences (1.3±0.3 vs 2.3±0.3, p = 0.09) were not statistically significant but suggest some improvement with the new information visualization tool. Despite the non-significant difference in total times to task completion (43±4 mins vs 36±4 mins, p = 0.35) we observed shorter times for two scenarios with the visualization tool, suggesting that the time-saving benefits may be more evident with certain clinical processes. Other observed effects of the tool include more intuitive navigation between patient details and increased efforts towards methodical synthesis of clinical documents.Conclusion: Our study provides some evidence that new information visualization in clinical notes may positively influence synthesis of patient information from EHR clinical documents. Our findings provide groundwork towards a more effective display of EHR clinical documents using advanced visualization applications.Citation: Farri O, Rahman A, Monsen KA, Zhang R, Pakhomov SV, Pieckiewicz DS, Speedie SM, Melton GB. Impact of a prototype visualization tool for new information in EHR clinical documents. Appl Clin Inf 2012; 3: 404–418http://dx.doi.org/10.4338/ACI-2012-05-RA-0017
Keywords: Electronic health records; data visualization; interfaces and usability